ANALISIS DESAIN INSTITUSI INTERNASIONAL MERCOSUR - , IVAN NASHARA H. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Regionalism is a worldwide trend in international cooperation today. States works together with their neighbors to create an institutional cooperation encompassing diverse issues from economy to politic. Mercosur is one of those regionalism which formed in Latin America in 1991. Joined by Brazil, Argentine, Paraguay, Uruguay, Venezuela, Bolivia, and several other associate members, Mercosur is the biggest regional economy in South America surpassing other regional institution such as Comunidad Andina and ALBA. In the diversity of regional institution in South America, Mercosur emerged as an unique institution with their own pattern, structure, vision, and norms. This Thesis analyze the rational design of international institution which applied in Mercosur by describing the structure, system, and explaining rational reason on why the design was chosen and has been developing. The analyzis came from assumption that institutional design has been formed by formulation of the member stateâs national interest.